Pengolahan Sandwich Buah Sebagai Salah Satu Makanan Bergizi Dalam Upaya Meningkatkan Gizi Keluarga Di Desa Teluk Lecah - Herry Daniel Marbun; Jusmarni Jusmarni; Nurhalimah Nurhalimah; Susi Pradasari; Sri Wahyuni; Marfel Aditia Manurung; Putri Fadilla Sari; Ulfaniati Ulfaniati; Salsa Amalia (Institut Nalanda, 2023)
Fruit sandwiches are a food that is popular at breakfast or just as a snack. Sandwiches are made from two pieces of bread sandwiched with fruit filling according to individual tastes, to make it more delicious, some people also often add mayonnaise and chili sauce (Aliza, 2011). Sandwiches or sandwiches are very popular because they are liked by many people, from children to the elderly, and they are relatively easy to make. Sandwiches can also be used to entertain guests who come to the house (Kirana, 2009). The aim and objective of the nutritious food management program in Teluk Lecah Village is to help mothers process healthy food to serve to their families. The target that mothers want to achieve after participating in this socialization is that mothers understand how to make good and correct food. Providing knowledge for mothers in preparing healthy food will support the success of this program.